COCONUT BISEXUAL FLOWERS AND THEIR SIGNIFICANCE FOR HYBRID SEED GARDENS - T.A. Davis; R.B. Maliangkay (International Coconut Community, 1988)
Among the tall and dwarf varieties of coconut as well as the hybrids between them, occasionally one comes across hermaphrodite or bisexual flowers. Some indNridual palms produce a high percentage of hermaphrodite flowers while a great majority of others do not produce any bisexual flower at all. There is clear evidence that coconut flowers at the primordial stage are bisexual with the potential. to develop both stamens and pistils in the same flower. But at a later stage of development, one grows into a female flower whose male organs are reduced to a ring of six staminodes. Another develops into a staminate flower whose pistils are reduced to three pistillodes. However, due to genetic, ecological, physiological or other factors, some unisexual. flowers show an atavistic display of hermaphroditisin. Bisexual flowers are observed among tall. and dwarf variety palms. The negligible percentage of bisexual flowers that occur in large estates where the fruits are not used as seeds has no major disadvantage. But in seed gardens, especially where inter‑varietal hybrid seeds are produced, hermaphrodite flowers are capable of reducing the percentage of true hybrids. Timely removal of hermaphrodite flowers, therefore, would reduce the occurrence of undesirable true‑to‑mother type progeny and enhance the success of intervarietal hybridization.